Flowers of Deceptive Aristolochia microstoma Are Pollinated by Phorid Flies and Emit Volatiles Known From Invertebrate Carrion - Rupp, Thomas; Oelschlägel, Birgit; Rabitsch, Katharina; Mahfoud, Hafez; Wenke, Torsten; Disney, R. Henry L.; Neinhuis, Christoph; Wanke, Stefan; Dötterl, Stefan (Frontiers in Ecology and Evolution, 2021)
Deceptive flowers decoy pollinators by advertising a reward, which finally is not provided. Numerous deceptive plants are pollinated by Diptera, but the attractive cues and deceptive strategies are only identified in a few cases. A typical fly-deceptive plant genus is Aristolochia, which evolved sophisticated trap flowers to temporarily capture pollinators. Though rarely demonstrated by experimental approaches, Aristolochia species are believed to chemically mimic brood sites, food sources for adult flies, or utilize sexual deception. Indeed, for most species, studies on scent composition and attractive signals are lacking. In this study, we focused on A. microstoma, a peculiar Greek endemic with flowers that are presented at ground level in the leaf litter or between rocks and are characterized by a unique morphology. We analyzed flower visitor and pollinator spectra and identified the floral scent composition using dynamic headspace and gas chromatography coupled to mass spectrometry (GC/MS). Female and male phorid flies (Phoridae) are the exclusive pollinators, although the flowers are also frequently visited by Sciaridae, as well as typical ground-dwelling arthropods, such as Collembola and arachnids. The carrion-like floral scent mainly consists of the oligosulphides dimethyldi- and dimethyltrisulfide, and the nitrogen-bearing compound 2,5-dimethylpyrazine. These three compounds together are known to be released from decomposing insects, and thus, we conclude that pollinators are likely deceived by chemical imitation of invertebrate carrion, a deceptive strategy not described from another plant species so far.